Piccolo Corso Informale di Statistica: Presentazione Generale - Michele Nichelatti; Maurizio Nordio; Umberto Maggiore; Aurelio Limido (AboutScience Srl, 2018)
Abstract non disponibile (Epidemiology_statistics)